In vitro and in vivo genotoxicity and cytotoxicity analysis of protein extract from Aplysina fulva sponges - Alan de França Santana; Ingrid Regina Avanzi; Julia Risso Parisi; Matheus Almeida Cruz; Giovanna Caroline Aparecida do Vale; Tiago Akira Tashiro de Araújo; Samuel Rangel Cláudio; Daniel Araki Ribeiro; Renata Neves Granito; Ana Claudia Muniz Renno (Acta Scientiarum: Biological Sciences, 2021)
This study evaluated the physicochemical and morphological properties of a marine sponge protein extract (PE) using scanning electron microscopy (SEM), Energy dispersive X-ray spectroscopy (EDS), analysis of mass loss and pH and in vitro and in vivo. Scanning electron microscopy showed that PE fibers present a granular aspect and irregular structure and the element carbon followed by oxygen was detected in the EDS analysis. Moreover, a 29% of mass loss was observed after 14 days and the pH slightly modified after 14 days. Cell viability of fibroblast cells (L929) of control and PE at a concentration of 25% demonstrated higher values compared to the groups. Osteoblast cell viability of PE at 25 and 50% was significantly higher. Comet assay on day 1 showed higher values for PE at 25%. In addition, in vivo experiments demonstrated that in the treated animals, the bone defects were filled with biomaterial particles, granulation tissue and some areas of newly formed bone. Furthermore, similar immunoexpression of Runx-2 and Cox-2 was observed. Taken together, all results suggest that PE is biocompatible, present non-citotoxicity in the in vitro studies (at the lower concentration) and in the in vivo studies and it can be considered as an alternative source of collagen for tissue engineering proposals.